2012
DOI: 10.1002/wsb.226
|View full text |Cite
|
Sign up to set email alerts
|

Small mammal use of field borders planted as beneficial insect habitat

Abstract: Field borders established for wildlife conservation have been recognized as a possible venue for also promoting beneficial insect populations, such as parasitic wasps and pollinators, on agricultural lands. However, traditional fallow field borders lack nectar sources required to sustain beneficial insect communities, and their value to small mammals is not well‐understood. In October–November 2009, we trapped small mammals in four field‐border treatments (planted native, warm‐season grasses and prairie flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Where tall grass was found to interfere with feeding and ground movement of birds, it also provides nesting sites and food diversity for other species (Barras & Seamans 2002). Mowing, or other means of reducing grass cover, has been found to reduce small mammal cover and food at airports (Blackwell et al 2013) and to decrease populations in general (Birney et al 1976;Edge et al 1995;Peles & Barrett 1996;Washburn & Seamans 2007;Garrett et al 2012;Moorman et al 2013). In the present study the significantly lower abundance of small mammals in mown compared to unmown transects at both airports, particularly in the non-growing seasons, indicates the effectiveness of mowing to reduce small mammal presence.…”
Section: Discussionmentioning
confidence: 99%
“…Where tall grass was found to interfere with feeding and ground movement of birds, it also provides nesting sites and food diversity for other species (Barras & Seamans 2002). Mowing, or other means of reducing grass cover, has been found to reduce small mammal cover and food at airports (Blackwell et al 2013) and to decrease populations in general (Birney et al 1976;Edge et al 1995;Peles & Barrett 1996;Washburn & Seamans 2007;Garrett et al 2012;Moorman et al 2013). In the present study the significantly lower abundance of small mammals in mown compared to unmown transects at both airports, particularly in the non-growing seasons, indicates the effectiveness of mowing to reduce small mammal presence.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits can be particularly important after disturbances caused by agricultural practices like tillage, pesticide application and harvesting (Lee, Menalled & Landis, 2001). Field margin establishment and management is one of the affordable measure by a majority of the farmers due to the associated multiple benefits including biodiversity, conservation and functional values (Moorman et al, 2013). Understanding the various benefits of field margin and non-crop vegetation in agriculture and environment is particularly important for proper management.…”
Section: Andmentioning
confidence: 99%
“…Small mammals studied in the context of field margin and adjacent vegetation include the harvest mouse, Reithrodontomys megalotis (Canády, 2013;Sullivan & Sullivan ,2006), several mole species (Talpidae) (Zurawska-Seta & Barczak, 2012), house mouse, Mus musculus (Sullivan & Sullivan, 2006;Moorman et al, 2013), deer mouse, Peromyscus maniculatus, Great Basin pocket mouse, Perognathus parvus and various vole species (Sullivan & Sullivan, 2006).…”
Section: Enhanced Survival Of Small Mammalsmentioning
confidence: 99%
“…tion was never hayed in wildlife fields, so food and cover remained continuously available. Similarly, Moorman et al (2013) reported large numbers of cotton rat captures in field borders planted with native warm-season grasses and wildflowers that retained food and cover throughout the growing season, and they reported no captures in mowed borders where resources were removed. House mice and white-footed mice are omnivorous habitat generalists; therefore, plant community composition likely is of less importance to these species than it is to herbivorous cotton rats (Whitaker 1966, Randolph et al 1991.…”
Section: Model Effectsmentioning
confidence: 99%
“…Incorporating both native warm-season and cool-season forage as separate but adjacent units or fields in the same forage production system will provide a continual highquality forage resource and provide small mammals with nearby escape cover because the 2 field types should be hayed at different times. Additionally, leaving small fields or field borders unharvested will create refugia for small mammals after cover is removed from forage fields (Moorman et al 2013).…”
Section: Model Effectsmentioning
confidence: 99%